Contextualization of Polygamy Law; Justification of Islamic Legal Principles against Positive Regulations in Indonesia - Nur, Muhammad; Tanjung, Dhiaudin (State of Islamic Institute Langsa, 2024)
Ideally, polygamy law in Islam sets a maximum limit of four wives, requires the husband to act justly, and considers material and emotional factors, as stipulated in the Qur'an. However, in reality, there are differences in the implementation of the law in Indonesia. Law No. 1 of 1974 does not limit the number of wives, while the Compilation of Islamic Law (KHI) limits it to four wives and requires the wife's consent, which must be proven in court. These differences reflect a discrepancy between Islamic legal principles and current positive regulations. This article aims to provide a deeper understanding of the differences between polygamy law in Islam and positive regulations in Indonesia. This research uses a comparative approach with a literature study method to analyze and compare Islamic legal principles with positive regulations in Indonesia related to polygyny. The results show that over time and with changes in the state system, the contextualization of polygamy law has undergone justification and rationalization, leading to significant changes in its application.